FEAR OF BREATHING, FEAR OF DEPENDENCE: LAPORAN KASUS GANGGUAN ANXIETAS ORGANIK PADA PASIEN MYASTHENIA GRAVIS PASCATIMEKTOMI DENGAN KETERGANTUNGAN VENTILATOR - Karouw, Grace Venny Febe; Kurniawan, Lely Setyawati; Aryani, Luh Nyoman Alit; Mahardika, I Komang Ana (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2025)
Patients with Myasthenia Gravis (MG) undergoing thymectomy are at risk of developing postoperative respiratory complications requiring mechanical ventilation. This dependence may lead to severe paradoxical anxiety, characterized by both fear of breathing (anxiety about ventilator removal) and fear of dependence (fear of lifelong reliance on mechanical support). This narrative review analyzed recent literature from the past decade, focusing on neuropsychiatric perspectives of ventilator dependence in MG patients. Fear of breathing involves hyperactivation of brain structures such as the amygdala and insular cortex, resulting in anticipatory dyspnea. Fear of dependence stems from existential anxiety linked to loss of autonomy and identity, mediated by dysregulation in the ventromedial prefrontal cortex and default mode network. These fears contribute to a maladaptive cycle involving learned helplessness and avoidance behavior. Early psychiatric evaluation, cognitive behavioral therapy (CBT), and low-dose SSRI pharmacotherapy have shown promising outcomes. Multidisciplinary collaboration is essential to optimize psychophysical recovery and reduce ICU length of stay. Paradoxical respiratory anxiety in MG patients presents a significant barrier to ventilator weaning and recovery. Integrated psychiatric interventions are crucial to address both physiological and psychological needs, ensuring holistic care in critical settings. ABSTRAKPasien dengan Myasthenia Gravis (MG) yang menjalani tindakan timektomi sering menghadapi komplikasi pernapasan yang memerlukan dukungan ventilator. Ketergantungan ini dapat memunculkan kecemasan berat yang paradoksal, yakni rasa takut saat ventilator dilepas (fear of breathing) dan kecemasan terhadap ketergantungan jangka panjang pada alat bantu napas (fear of dependence). Studi tinjauan pustaka menggunakan literatur dari jurnal internasional yang terbit dalam 10 tahun terakhir, dengan fokus pada aspek neuropsikiatri pasien MG dengan ventilator dependence. Fear of breathing melibatkan disregulasi sistem saraf pusat (amigdala, insula, prefrontal cortex) yang memperkuat anticipatory dyspnea. Sementara itu, fear of dependence muncul dari ketakutan eksistensial akan kehilangan otonomi dan harga diri. Kedua bentuk kecemasan ini memperburuk prognosis melalui siklus learned helplessness dan anxiety-avoidance. Pendekatan psikiatri berbasis Cognitive Behavioral Therapy (CBT), farmakoterapi selektif, dan keterlibatan tim multidisiplin telah terbukti mempercepat pemulihan. Kecemasan respiratorik paradoksal merupakan tantangan penting dalam perawatan pasien MG. Intervensi psikiatri terintegrasi diperlukan untuk mendukung keberhasilan weaning dan menjaga kesehatan mental pasien.